2017
DOI: 10.1007/s00572-017-0800-1
|View full text |Cite
|
Sign up to set email alerts
|

Soil spore bank communities of ectomycorrhizal fungi in endangered Chinese Douglas-fir forests

Abstract: Chinese Douglas-fir (Pseudotsuga sinensis) is an endangered Pinaceae species found in several isolated regions of China. Although soil spore banks of ectomycorrhizal (ECM) fungi can play an important role in seedling establishment after disturbance, such as in the well-known North American relative (Pseudotsuga menziesii), we have no information about soil spore bank communities in relict forests of Chinese Douglas-fir. We conducted bioassays of 73 soil samples collected from three Chinese Douglas-fir forests,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 55 publications
1
4
1
Order By: Relevance
“…cajanderi roots at the treeline ( Miyamoto et al, 2022 ). This reduction is comparable to those reported in previous studies that performed bioassay experiments in temperate and boreal forests (12-45%) ( Glassman et al, 2015 ; Miyamoto & Nara, 2016 ; Murata et al, 2017a ; Wen et al, 2018 ).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…cajanderi roots at the treeline ( Miyamoto et al, 2022 ). This reduction is comparable to those reported in previous studies that performed bioassay experiments in temperate and boreal forests (12-45%) ( Glassman et al, 2015 ; Miyamoto & Nara, 2016 ; Murata et al, 2017a ; Wen et al, 2018 ).…”
Section: Discussionsupporting
confidence: 90%
“…geophilum was reduced at KTY, perhaps due to soil conditions or other environmental factors rather than distance effects because this species is a common EM associate of tundra shrubs ( Miyamoto et al, 2022 ). Although we did not detect distance effects between the two sites, the overall fungal colonization rates were lower in this tundra (28.6%) than in similar bioassay experiments conducted in mature forests (57-100%; Miyamoto & Nara, 2016 ; Murata et al, 2017a , b ; Wen et al, 2018 ). Several bioassay studies have reported reduced EM colonization from soils collected beyond host range limits at local (1-3 km) and regional (~300 km) scales ( Nuñez et al, 2009 ; Fujiyoshi et al, 2011 ; Reithmeier & Kernaghan, 2013 ; Pickles et al, 2015 ), primarily due to dispersal limitation of the fungal propagules ( Peay et al, 2012 ).…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…Spore banks can be important in providing compatible ECM fungi to seedlings in temperate forests (e.g. Wen et al., ), but their roles in boreal forests are poorly known.…”
Section: Introductionmentioning
confidence: 99%
“…densiflora and Betula maximowicziana [ 28 ], P . muricata in fire-disturbed forest soils [ 28 , 29 ], Pseudotsuga sinensis [ 30 ] and P . bungeana [ 31 ], but abundant in some pine forests at north America [ 10 ].…”
Section: Discussionmentioning
confidence: 99%